Negative transfer from Spanish to English in vowels /ʌ/ and /æ/ - Cid, Luis (Íkala, Revista de Lenguaje y Cultura, 2017)
The aim of this non-experimental descriptive study is to establish if linguisticnegative transfer caused by the aural perception of Spanish vowel phonemesis responsible for spelling mistakes found in 5th graders’ written texts from aSpanish-English bilingual school in Concepción, Chile. The subjects of thisstudy participated in an aural perception test in which they had to representthe English vowels /ʌ/ and /æ/ —these vowels were presented in twelve pseudowords. The results are consistent with the literature on the subject of phonetic-phonological negative transfer, suggesting the influence of Spanish phonicson the auditory vowel perception in English, both for pseudo words within asemantic context and in isolation.